Motivating factors for and barriers to the COVID-19 vaccine uptake: A review of social media data in Zambia - Tulani Francis L. Matenga; Joseph Mumba Zulu; Lwendo Moonzwe Davis; Malizgani Paul Chavula (Taylor & Francis Group, 2022)
The study sought to explore the motivating factors for and barriers to the uptake of the coronavirus disease 2019 (COVID-19) vaccine in Zambia and recommend possible ways of addressing the challenges. The study used a qualitative case study approach, employing online media platforms as sources of data. Thematic analysis was to identify topics from posts, with each topic further grouped into themes. Motivating factors to vaccine uptake include an increase in reported cases of COVID-19, accessibility, and availability of vaccines, vaccine certificates required to travel, and credible sources of information. Barriers to uptake include lack of information, concerns about the safety of the vaccine, mistrust in Western medicine, lack of belief in conventional medicine versus belief in God, confusing information about eligibility, and belief that public figures used in the campaigns were not receiving the vaccine. Some of the strategies to encourage vaccination included the involvement of local scientists, demand generation through media platforms, community sensitization, vaccine materials, and creating an enabling environment for community involvement. The social media interactions on the COVID-19 vaccine revealed several factors that impede the uptake of the vaccine and encourage uptake. However, stakeholders' involvement in scaling up vaccination programs was reported to be one of the effective strategies to increase vaccine uptake in Zambia.